2014
DOI: 10.1007/s10329-014-0439-x
|View full text |Cite
|
Sign up to set email alerts
|

Double invisible displacement understanding in orangutans: testing in non-locomotor and locomotor space

Abstract: The nonadjacent double invisible displacement task has been used to test for the ability of different species to mentally represent the unperceived trajectory of an object. The task typically requires three occluders/boxes in a linear array and involves hiding an object in one of two nonadjacent boxes visited in succession. Previous research indicates that 19-, 26-, and 30-month-old children and various nonhuman species cannot solve these displacements. It has been hypothesized that this is because individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As they wrote, "If subjects were not able to solve the problem of tracking the displacement of the food under these circumstances, they could not solve the false belief problem either" (p. 391). Although some great apes had to have a modified invisible displacement control in Call and Tomasello (1999), other apes have successfully passed switch invisible displacement trials with blinding as well as more complex tests of double invisible displacement (as reviewed by Jaakkola, 2014;Mallavarapu, Stoinski, Perdue, & Maple, 2014). Tschudin's studies (2001Tschudin's studies ( , 2006 were some of the first tests of object permanence in dolphins.…”
Section: Pre-requisite Abilities Assumed: Invisible Displacement Memory Attention Spanmentioning
confidence: 99%
“…As they wrote, "If subjects were not able to solve the problem of tracking the displacement of the food under these circumstances, they could not solve the false belief problem either" (p. 391). Although some great apes had to have a modified invisible displacement control in Call and Tomasello (1999), other apes have successfully passed switch invisible displacement trials with blinding as well as more complex tests of double invisible displacement (as reviewed by Jaakkola, 2014;Mallavarapu, Stoinski, Perdue, & Maple, 2014). Tschudin's studies (2001Tschudin's studies ( , 2006 were some of the first tests of object permanence in dolphins.…”
Section: Pre-requisite Abilities Assumed: Invisible Displacement Memory Attention Spanmentioning
confidence: 99%
“…Field researchers have reported that wild orangutans are adept at finding food despite irregular temporal and spatial distributions of fruit in their natural habitats (Galdikas & Vasey, 1992), and extractive foraging tasks in captive settings have similarly showed orangutans to be efficient foragers (MacDonald & Agnes, 1999). However, mixed results from cognitive studies in laboratory settings suggest some constraints on orangutans’ ability to flexibly adjust their search strategies to solve experimental visuospatial memory tasks (Call, 2001; Mallavarapu et al, 2014; Washburn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The former method includes Piagetian visible and invisible displacement tasks, which examine subjects’ capacities to understand object permanence as it relates to the mental representation of unperceived objects and their trajectories (Piaget, 1954; Tomasello & Call, 1997). Despite success on some displacement tasks, mixed results have shown that orangutans have difficulty finding occluded food that has been sequentially and invisibly displaced by an experimenter across multiple nonadjacent containers (Call, 2001; Barth & Call, 2006; De Blois et al, 1998; Mallavarapu et al, 2014). To account for these errors, authors have posited explanations ranging from general memory deficits to difficulties with inhibiting responses toward salient distractor choice locations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations